Relationship Between Perceived Organizational Support With Turnover Intention In Female Employees - Islamiyati, Himmatul; Sahrah, Alimatus (Utan Kayu Publishing, 2022)
One way that must be taken to survive and compete is to maintain and empower human resources. This study aims to determine the relationship between perceived organizational support and turnover intention of female employees in DKI Jakarta. The research subjects were 118 female employees in DKI Jakarta who work in private companies. The data collection method in this study used was the turnover intention scale and perceived organization support scale. The data were analyzed using the product-moment correlation test, the results showed the magnitude of the correlation coefficient of (rxy) = -0.547 with p = 0.000 (p less than 0.050). This shows a negative relationship between perceived organizational support and turnover intention of female employees in DKI Jakarta, hypothesis in this research was accepted. Abstrak. Salah satu cara yang harus diambil agar perusahaan bisa bertahan dan bersaing adalah dengan mempertahankan dan memberdayakan sumber daya manusia. Penelitian ini bertujuan untuk mengetahui hubungan antara perceived organizational support dengan turnover intention pada karyawan wanita di DKI Jakarta. Subjek dalam penelitian berjumlah 118 orang dengan karakteristik karyawan wanita yang berlokasi tempat kerja di DKI Jakarta dan bekerja di perusahaan swasta. Metode pengumpulan data dalam penelitian ini menggunakan skala turnover intention dan skala perceived organizational support. Data dianalisis dengan menggunakan uji korelasi product moment, hasilnya menunjukkan besarnya koefisien korelasi sebesar (rxy) = -0,547 dengan p = 0,000 (p kurang dari 0,050). Hal ini menunjukkan bahwa terdapat hubungan negatif antara perceived organizational support dengan turnover intention pada karyawan wanita di DKI Jakarta, sehingga hipotesis diterima.